2020
DOI: 10.1155/2020/2653096
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Provincial Dwellers on Prevention and Control of Schistosomiasis: Evidence from a Community-Based Cross-Sectional Study in the Gambia

Abstract: Background. Socioeconomically disadvantaged and neglected communities were found to be the most affected groups for schistosomiasis as a result of inadequate safe water and sanitation facilities. In order to inform policies and practices, the present study examined the influence of sociodemographic factors and attitudes on the knowledge and practice in the prevention and control of schistosomiasis in eighteen endemic rural communities in the Gambia. Methods. In January 2019, a community-based cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
5
12
1
Order By: Relevance
“…This study shows that livestock farmers in all regions and of all ages are aware of AAT and how to control the disease in their animals. This finding is similar to previous studies by Barrow et al [ 29 ], who also reported that there was a higher significance of age and gender in practices that control and prevent schistosomiasis in The Gambia. Finally, 84% of livestock owners reported expending US$ 2 and 16% expending US$ 3 to treat one of their cattle suspected of having trypanosomiasis depending on the severity of the animal's ailment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study shows that livestock farmers in all regions and of all ages are aware of AAT and how to control the disease in their animals. This finding is similar to previous studies by Barrow et al [ 29 ], who also reported that there was a higher significance of age and gender in practices that control and prevent schistosomiasis in The Gambia. Finally, 84% of livestock owners reported expending US$ 2 and 16% expending US$ 3 to treat one of their cattle suspected of having trypanosomiasis depending on the severity of the animal's ailment.…”
Section: Discussionsupporting
confidence: 92%
“…This study shows that livestock farmers in all regions and of all ages are aware of AAT and how to control the disease in their animals. This finding is similar to previous studies by Barrow et al [29], who also reported that there expending US$ 3 to treat one of their cattle suspected of having trypanosomiasis depending on the severity of the animal's ailment. The burden of treatment for this disease further helps to impoverish livestock owners in The Gambia.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted among 383 household heads in Kuntaur and Janjanbureh Local Government Areas (LGAs) in Central River Region found 54.3% had poor knowledge and fair (57.7%) practices toward prevention and control of schistosomiasis [13]. Whereas very positive (96.9%) attitude were revealed toward schistosomiasis control.…”
Section: Community Member's Knowledge Attitude and Practices About Sc...mentioning
confidence: 99%
“…It was also found that older community members were found to be more likely to have good knowledge on schistosomiasis prevention and control in these communities. Male residents were more likely to have good practice towards schistosomiasis prevention and control in the rural Gambia [13]. Besides, another study among school aged children in rural Gambia which included communities in CRR had revealed that being a male, you are more likely at-risk of S. haematobium infection compared to females, though bathing, playing and swimming in water bodies were found to pose less risk for S. haematobium infection [12].…”
Section: Community Member's Knowledge Attitude and Practices About Sc...mentioning
confidence: 99%
“…The Gambia is located in the tropical sub-humid ecoclimatic zone, with annual rainfall ranging from 800 to 1200 mm annually (Jaiteh 2017). There are two seasons in the climate: a rainy season (June to October) and a dry season (November to April), which is six to seven months without rain (Barrow et al, 2020), During the dry season, the climate is dominated by dry, dusty winds that originate from the Sahara Desert (Jaiteh 2017). A total of twelve districts where included in this study and all of them are in the rural areas of The Gambia.…”
Section: Study Locationmentioning
confidence: 99%